Developing Moodle-based e-learning on the topic of logarithm for the tenth-grade students of SMA N 1 Sewon - Nor Hasanah; Uswatun Khasanah (Universitas Ahmad Dahlan, 2021)
The development of technology and communication has an impact on all aspects of life, including in the learning process using media. This study aims to develop e-learning platform by using Moodle on logarithmic material for ten grader students of SMA Negeri 1 Sewon. This development research uses the ADDIE model. The subjects of this study were learning material expert, learning media expert, and 10 grader students of SMA Negeri 1 Sewon. Data collection techniques were carried out by interviews, questionnaires, and observations. The data analysis techniques were conducted by converting qualitative data into quantitative data using a Likert scale. The results obtained from experts in the material included in the feasible category, the results obtained by media experts included in the feasible category, and the results of student assessment obtained as a feasible category. Based on these results, it can be concluded that the learning media developed can be used in the process of learning mathematics.